Penerapan Biaya Diferensial dalam Pengambilan Keputusan Menyewa Atau Membeli Aset Tetap (Alat Musik) - Ameillyana Puji Hapsari; Fauziyah Fauziyah; Imarotus Suaida (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
This study aims to determine the Application of Differential Costs in Decision Making to rent or buy fixed assets (musical instruments) in the field of musical instrument rental. This type of research is quantitative research. Data is obtained through primary and secondary data. This research was conducted in 2020 to 2022. Data collection techniques through interviews and documentation. Data analysis techniques are carried out by identifying data on interview costs, observations and documentation at the New Arista Orchestra. Based on the results of the analysis, these relevant costs can be used as considerations for the company in making decisions. With the alternative of buying, it will save costs of IDR 76,257,322.93 or 2.7% in making decisions with the alternative of buying or renting heavy equipment, it is better to consider the expenses that will be incurred from the two alternatives with relevant costs so that the decisions taken can benefit the company. The results of the comparison using the differential costs above. it can be concluded that differential cost analysis is very useful for the new Orchestra in making better decisions taken by the orchestra is to buy because it is more profitable than renting musical instruments.